Transient endocrine pancreatic insufficiency secondary to severe pediatric acute necrotizing pancreatitis - Virú-Loza, Manuel André (2023)
As a result of acute pancreatitis (AP), there may be subsequent diabetes or transient hyperglycemia during the episode of AP. The incidence of AP in pediatric age is up to 12.2 cases per 100,000 children per year and only 4 to 5% later develop diabetes. Regarding transient hyperglycemia in children, information is scarce, and no publications have been made about it in our country. The case of a girl with transient hyperglycemia secondary to severe necrotizing AP is reported. It is important to constantly monitor glucose levels and timely manage hyperglycemia in children with AP since, at least in adults, it is associated with severe AP and higher mortality.